MARKERS OF BONE METABOLISM IN PATIENTS WITH CYSTIC FIBROSIS. - Bojana Naydenova- Stoeva (Peytchinski Publishing, 2015)
Aim: Some scientific studies show decreased bone mineral density and increased fracture frequency in patients with cystic fibrosis. The mechanism for early bone loss in CF patients are multifactorial: chronic pulmonary inflammation, malnutrition, reducer physical activity, delayed pubertal maturation. The aim of this study was to assess bone metabolism markers in patients with cystic fibrosis and compare them with these in healthy controls. Material and Methods: We examined 44 patients with cystic fibrosis with average age 14,7 years. The control group consist 43 healthy controls with average age 13,8 years. The levels of bone markers- N Mid Osteocalcin and β Cross Laps in the serum were examined by electro-chemiluminescence method- ECLIA; serum alkaline phosphatase (AP)- kinetic method; common and ionized calcium- atomic-absorption method. The statistical processing of data is made with SPSS programme- version 16.0. Results: It was established a statistically significant and increased levels of the markers of bone formation in patients, probably as a compensative reaction of the organism to the increased bone resorption (comparing the median levels of β Cross Laps in the two groups). This difference stays constant when only men from the two groups were compared, while there is no such difference between women. Only in the group of patients-men there is a significant evaluated levels of β Cross Laps, compared with the mediate levels in patients-women and less increased N Mid Osteocalcine and AP. Increasing the age of patients, the levels of the investigated markers i.e. N Mid Osteocalcine decrease. This is not found out in the group of the controls. N Mid Osteocalcine is in positive relation with AP in the two groups, and that confirms the fact that the growth of AP returns for its bone fraction. The increase of β Cross Laps is related with the increase of N Mid Osteocalcine. Conclusion: In patients with cystic fibrosis changes in the profile of bone metabolism were observed. The patients should be under a comprehensive medical and nutritional care in order to achieve their optimal peak bone mass.